Socioeconomic Status and HIV duration as Determinants of Vitamin D Deficiency in HIV Patients - UMAR TANVEER; EJAZ ASGHAR; TASAWAR AZIZ; ASIFA ZEBA; NAYAB TANVEER; FOUZIA ABDUL RAZZAQ; FATMA HILAL YAGIN (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Vitamin D deficiency is a common issue in HIV-infected individuals, with significant implications for immune function and overall health. Socioeconomic status (SES) and the duration of HIV/AIDS are potential factors influencing vitamin D levels, but their exact roles remain underexplored. This study aimed to assess the relationship between SES, the duration of HIV/AIDS, and vitamin D deficiency in HIV-infected patients. Methods: This cross-sectional study was conducted between 15 January 2024 and 15 March 2025 in Sindh on 120 patients living with HIV. Information on socioeconomic status, duration of HIV infection, antiretroviral therapy regimens, and clinical characteristics was collected. Serum vitamin D levels were measured, and logistic regression analysis was performed to identify factors associated with vitamin D deficiency. Results: Of the 120 participants, 75% had vitamin D deficiency. A significant inverse relationship was found between the duration of HIV infection and vitamin D levels (p = 0.03). No significant correlation was found between SES and vitamin D deficiency (p = 0.29). Logistic regression analysis indicated that longer disease duration (OR = 1.75) and lower SES (OR = 1.45) were associated with higher odds of vitamin D deficiency. Conclusion: While SES did not significantly affect vitamin D deficiency, the duration of HIV infection was a significant determinant. Routine screening and vitamin D supplementation are recommended for HIV-infected patients, especially those with longer disease durations.